Operations and Maintenance Practices and their Impact on Power Plant Performance - Shyong, F.; Terziovski, Mile (Academy of Management, 2008)
The aim of the study was to examine the impact of Operations and Maintenance (O&M) practices, individually and collectively, on power plant pe1formance. Data were collected from more than 100 power plants in Australia and Malaysia. The reliability and validity (content, construct, and criterion) of the practice and performance measures were evaluated. Our study showed that the relationship between O&M practices and plant performance is significant and positive in a cross-sectional sense. Both people-oriented "soft" as well technically-oriented as ''hard" practices were found to be positive and significant predictors of plant performance. This is consistent with literature on socio-technical systems theory that both "soft" and "hard" practices are required to complement each other to produce and sustain high performance. Among the practices, executive commitment and TPM-orientation are the strongest significant predictors of plant performance. Our findings also highlight the impact of maintenance practices on plant performance compared to other practices such as long-term planning, customer focus, knowledge management, and employee involvement. Based on our study we conclude that Total Quality Management (TQM) and maintenance philosophies are sources of sustainable competitive advantage in the power generation sector.